Grain yield and water productivity of maize under deficit irrigation and salt stress: Evidences from field experiment and literatures - Jia Gao; Lin Li; Risheng Ding; Shaozhong Kang; Taisheng Du; Ling Tong; Jian Kang; Wanli Xu; Guangmu Tang (Agricultural Water Management)
Drought and salt stress pose great challenges to global agriculture, yet mild deficit irrigation and salt stress have the potential to enhance water productivity (WP). However, it is not desirable to improve WP by reducing irrigation if it leads to a decrease in yield. This study aimed to investigate the effects of deficit irrigation and salt stress on maize yield and WP, as well as the underlying mechanism, and to explore agronomic practices to jointly improve maize yield and WP based on literature analysis. To achieve this, we conducted a 2–year field experiment with two maize genotypes (ZD958 and XY335), involving two irrigation levels (F: full irrigation and D: deficit irrigation, 65 % ET/80 % ET) and two salt levels (S0: no salt and S1: 2 ‰). Additionally, we performed a synthesis analysis of peer–reviewed literature to assess the effects of deficit irrigation and/or salt stress on maize yield, evapotranspiration and WP. Our results showed that both deficit irrigation and salt stress increased leaf intrinsic water use efficiency (WUEi) and WP. Compared to the control (FS0), WP significantly increased by 11.5 % in DS0 and by 9.6 % in FS1, while decreased by 3.5 % in DS1. Furthermore, the increase in WP under single water and salt stress was attributed to the reduction in ET, while the decrease in WP under combined stress was attributed to the negative effect on grain yield. Both deficit irrigation and salt stress had adverse effects on leaf morpho–physiological traits and dry matter accumulation, with salt severely inhibiting the recovery ability after rewatering. Literature analysis showed that deficit irrigation increased WP by 10.5 %, and when coupled with agronomic practices such as controlled–release fertilizers and mulching, WP improved by 19.2 % without reducing the grain yield of maize. Deficit irrigation coupled with agronomic practices can achieve a win–win situation for both maize yield and WP. This study provides valuable insights into improving irrigation practices dealing with water shortages and salt stress in arid and semi–arid regions, further ensuring national food security.